UNWOMEN's Efforts to Abolish Honour Killing in Pakistan Through Transnational Advocacy Network Strategy - Contesa, Yenis; Muhammad, Ali (Journal of Islamic World and Politics, 2024)
This article aims to analyze UNWOMEN's efforts toward the elimination of honor killings in Pakistan. This article used the conceptual framework of transnational advocacy networks introduced by Keck and Sikkink. The research method of this article uses qualitative research with data sources from books, news, journal articles, official websites, and other supporting reports related to research needs. This research found that, first, information politics is carried out by collecting and disseminating information to raise public awareness through anti-violence programs. Secondly, symbolic politics involves using symbols and stories to influence public opinion and policy through various campaigns and slogans on social media. Third, leverage politics was used to pressure the Pakistani government through documentary films and appointing public figures as Goodwill Ambassadors. Finally, accountability politics focuses on monitoring the honor-killing phenomenon by implementing the principles of CEDAW. Then, there is a decrease in the number of honor killings, although not too significant, but it is the beginning of efforts to overcome honor killings in Pakistan. UNWOMEN's efforts aim to provide support and encouragement to the government and Pakistani society to jointly commit to eliminating honor killing. This article makes an important contribution to the role of international organizations in combating human rights violations in Pakistan.